2009
DOI: 10.1158/1541-7786.mcr-08-0147
|View full text |Cite
|
Sign up to set email alerts
|

Annexin-1 Regulates Growth Arrest Induced by High Levels of Estrogen in MCF-7 Breast Cancer Cells

Abstract: Estrogen, a naturally occurring female steroid growth hormone, has been implicated as a major risk factor for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 42 publications
3
41
1
1
Order By: Relevance
“…Breast carcinomas that are positive for estrogen and progesterone receptors have been shown to be ANXA1 negative (Cao et al, 2008), confirming previous reports that ANXA1 expression is lost in human breast cancer epithelial cells (Shen et al, 2005;Ang et al, 2009). However, triple negative, or estrogen receptor, progesterone receptor and Her2/neu negative breast cancers were to be ANXA1 positive (Cao et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Breast carcinomas that are positive for estrogen and progesterone receptors have been shown to be ANXA1 negative (Cao et al, 2008), confirming previous reports that ANXA1 expression is lost in human breast cancer epithelial cells (Shen et al, 2005;Ang et al, 2009). However, triple negative, or estrogen receptor, progesterone receptor and Her2/neu negative breast cancers were to be ANXA1 positive (Cao et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
“…ANXA1 has been reported to be reduced or lost in many cancers (Lim and Pervaiz, 2007). In breast cancer, however, reports are conflicting, where ANXA1 expression has been shown to be increased in some ductal carcinomas (Ahn et al, 1997;Pencil and Toth, 1998), but we and others have recently reported a loss of ANXA1 in breast carcinomas (Shen et al, 2006;Cao et al, 2008;Ang et al, 2009). Interestingly, ANXA1 was higher in metastatic tumors and lymph nodes compared with primary tumors (Shen et al, 2006), and ANXA1 is often identified as a metastatic biomarker in highly metastatic breast cell lines (Cicek et al, 2004;Kreunin et al, 2007).…”
Section: Introductionmentioning
confidence: 75%
“…The expression of certain of the non-ABC drug transporter proteins such as LRP and annexin A1 has been found to be increased after 17-β-estradiol treatment, as a consequence of the activation of the ER receptor. 22,23 To clarify whether the high efflux of doxorubicin in MCF-7 cells was due to non-ABC drug transport proteins, MCF-7 and MDA-MB-231 cells were treated with 17-β-estradiol overnight in culture medium containing steroid stripped serum (Sigma). The treated cells were analyzed for the expression of non-ABC drug transporter proteins by western blot, as well as functionally by measuring the efflux rate of doxorubicin.…”
Section: The Upregulation Of Lrp By Treatment Of Mcf-7 Cells With 17-mentioning
confidence: 99%
“…Annexin 1 is a lipocortin that is also involved in the inflammatory response (36). Annexin 1 is lost in clinical breast cancer, and data suggest that Annexin 1 may act as a tumor suppressor gene that modulates the proliferative functions of estrogens in breast cancer (37). There has been interest in the use of Annexin 1 as an anticancer therapy as it can be induced to block the NF-kB signal transduction pathway, which is exploited by cancerous cells in order to avoid cell death (38).…”
Section: Patient Characteristics-as Described Inmentioning
confidence: 99%